Isolation of Gram-positive Bacteria from Different Sources and Evaluation of their Probiotic Properties - Muhammad Faisal Shahbaz Akram; Muhammad Ashraf; Sultan Ali; Syeda Iqra Kazmi (Pasteur Institute of Iran, 2017)
Introduction: Probiotics are defined as live non-pathogenic microorganisms and if administered in adequate amounts, can have beneficial effects on their hosts. This study aimed to isolate Gram-positive bacteria from different sources and to evaluate their probiotic properties. Methods: We obtained five samples from various sources including yogurt, infant feces, cheese, and soil under aseptic methods. The samples were inoculated on MRS agar and M17 medium. Biochemical assays identified isolated bacteria. The probiotic effect of isolated bacteria was tested by applying acidic pH 2.0, 0.3% w/v bile salt concentration and gastric juice in the samples. The antibiotic susceptibility profiling and their antimicrobial effects against Escherichia coli, Staphylococcus aureus, Salmonella enterica and Pseudomonas aeruginosa, were determined. Results: Four Gram-positive bacteria including Lactobacillus acidophilus, Bifidobacterium bifidum, Lactococcus lactis and Bacillus subtilis were isolated from yogurt, infant feces, cheese, and soil, respectively. Except for B. subtilis, all the isolated bacteria were catalase-negative and non-motile. The results showed that viable count of L. acidophilus, B. bifidum, and L. lactis was significantly high (P<0.05), and B. subtilis was sensitive. The isolates showed an antimicrobial effect against all indicator pathogens except P. aeruginosa. The isolated B. subtilis showed no antimicrobial effect. The antibiotic susceptibility was determined for ten different antibiotics. All the isolates were susceptible to most of the antibiotics (table 6) and resistant to penicillin G, gentamicin, vancomycin, and kanamycin. Conclusion: The species L. acidophilus, B. bifidum, and L. lactis fulfilled the criteria for probiotic properties and can be used in field conditions as probiotics.